(untitled) (Research, Society and Development, 2023)
The main objective of this study is to discuss the importance of sexual visibility in elderly women. This is a systematic review of the literature which consists of developing an exhaustive research for a given topic to present the evidence found, where after searching the databases 15 articles were used for the construction of this research. Aging is an inevitable consequence, but old age does not limit sexual practice, quite the contrary, it should be encouraged as it promotes several health benefits, which include increased well-being and self-esteem, relieves pain, reduces stress, keeps the body active and improves memory. It is worth mentioning that it is extremely important that health professionals, especially nurses, since they are the ones who have the greatest contact with patients and the closest follow-up, have a relationship of trust with their patients and make use of health education. so that the main actions, benefits and guidance aid for good practice are said.